A new wideband regulated cascode amplifier with improved performance and its application. Issue 8 (August 2015) - Singh, Urvashi; Gupta, Maneesha; Srivastava, Richa
Abstract This paper presents a new high frequency Regulated Cascode (RGC) amplifier with improved performance. The split-length compensation technique is used to increase both the bandwidth and output impedance, and decrease the input impedance of the conventional RGC. The bandwidth of the proposed RGC amplifier is 5.81 GHz, which is about 2.7 GHz larger than that of simple one. The improved performance of the introduced circuit is achieved with no additional passive element and DC power dissipation. In the paper, output impedance and bandwidth of the proposed circuit are derived by using small signal analysis and have also been compared with the traditional one. In addition, a wideband high performance current mirror is designed in the work as an application of the proposed RGC structure. The bandwidth extension ratio (BWER) of the modified wideband current mirror is 1.37. The proposed circuits are designed by using TSMC 0.18 µm CMOS process and BSIM3 Level 49 device model. The circuits are simulated on Spectre simulator of Cadence to validate the analytical results obtained in the paper.